Clinical characteristics of schizophrenia, depression, and Alzheimer’s diseases among older adults: a retrospective study of 271 consecutive admissions - Wen Wang; Wen Wang; Wen Wang; Junrong Ye; Junrong Ye; Junrong Ye; Yanheng Wei; Yanheng Wei; Jiawei Huang; Jiawei Huang; Haoyun Wang; Fei Liu; et al. (Frontiers in Psychiatry)
ObjectiveThis study aims to identify the clinical characteristics of schizophrenia, depression, and AD among older adults.MethodsGeneral information of patients was collected, including diagnosis, age, gender, level of education, marital status, drinking behavior, smoking behavior, course of mental disorder, type of admission, history of modified electroconvulsive therapy (MECT) and hospitalization period. The Brief Psychiatric Rating Scale (BPRS), Geriatric Depression Scale (GDS), Generalized Anxiety Disorder 7-Item Scale (GAD-7), Insight and Treatment Attitudes Questionnaire (ITAQ), and Mini-Mental State Examination (MMSE) were employed to evaluate the participants’ mental status. The Functional Activities Questionnaire (FAQ), Social Support Rating Scale (SSRS), Barthel ADL Index, Standardized Swallowing Assessment (SSA), and Mini-Nutritional Assessment (MNA) were applied to measure social and daily living function. The Nurses’ Global Assessment of Suicide Risk (NGASR) and The Brøset Violence Checklist (BVC) were used to assess the patients’ risk of suicide.ResultsTotally 271 participants were recruited, the numbers of participants with schizophrenia, depression, and Alzheimer’s diseases (AD), were 81 (29.9%), 85 (31.4%), and 105 (38.7%), respectively. One-way ANOVA was used to compare the variance of the crude score results among three groups of subjects. The results showed that patients with depression had the highest GDS total score, followed by patients with AD, and patients with schizophrenia had the lowest score (P < 0.001). The total scores of GAD-7 and ITAQ in patients with depression were higher than those in patients with AD and schizophrenia (P < 0.001). The total score of MMSE in patients with schizophrenia and depression was higher than that in patients with AD (P < 0.001). The incidence of circulatory system diseases in patients with depression and AD was higher than that in patients with schizophrenia (P < 0.05). The incidence of respiratory system diseases in patients with AD was highest, followed by patients with schizophrenia, and patients with depression had the lowest incidence (P < 0.05). The incidence of nervous system diseases in patients with AD was highest, followed by patients with depression, and patients with schizophrenia had the lowest incidence (P < 0.05). The total scores of FAQ and SSA in patients with AD were higher than those in patients with schizophrenia and depression (P < 0.001), while patients with depression had statistically lower SSRS scores than patients with schizophrenia and patients with AD (P < 0.05). Furthermore, patients with AD had lower Barthel ADL Index scores and water-swallowing test (P < 0.001). MNA scores of patients with schizophrenia were higher than those of patients with depression and AD, with statistical significance (P < 0.05). The NGASR scores of patients with depression were higher than those of patients with schizophrenia and AD, which was statistically significant (P < 0.001). Patients with AD had the highest BVC total score, followed by that of patients with schizophrenia and patients with depression had lowest score, and the difference was statistically significant (P < 0.05).ConclusionsPatients with geriatric psychosis may experience abnormalities in various aspects that influenced daily living, including disorders of thinking, cognition, emotion, and behavior. Patients with schizophrenia have cognitive impairment. Cognitive training and medication are important. Patients with depression were considered to be at a greater risk for suicide compared to those with schizophrenia and AD. Active clinical measures must be adopted to improve patients’ depressive symptoms, change their suicidal attitudes, and enhance their self-confidence. Patients with AD were prone to respiratory and neurological diseases. Treatment of respiratory infections and hypoxia and other respiratory diseases would be necessary, and cognitive function training should be conducted. In addition, regarding to high risk of swallowing disorders and malnutrition, swallowing function training should be carried out to ensure food intake and prevent malnutrition. Driven by psychiatric symptoms, violent behavior was prevalent, thus effective communication and de-escalation techniques are needed. Although the symptoms of these three diseases are different, timely professional intervention and support from family members are urgently needed.